Rola służb specjalnych w demokratycznym państwie prawa - Grochowski, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The name of special services is applied to the civil and military services that organize and conduct intelligence and counterintelligence activities. Their operations are an element generating social and political trust between the political authorities and citizens. Given the current conditions of international relations and the international situation, a state is required to have efficient special services at its disposal. Anegative impact of globalization on state functioning, both in its external and internal dimensions, forces Polish special services to strengthen their fundamental function, that is providing information. The weakness of military intelligence and counterintelligence follows from the dissolution in 2000 of the Military Intelligence Services (WSI), and wasting their potential for political reasons. The role and task of special services in a democratic state should be to protect the liberty and democracy of the political system’s principles, as set out in the Constitution, instead of protecting particular interests. The nature of the transformations occurring in security circles in Poland and related globalization processes, as well as civilizational, cultural and technological changes and the emergence of a civil society, demand a different attitude to the special services to be taken both by the public authorities and society, and make changes in their functioning necessary. This also calls for the need for a theoretical interpretation of the operations of modern Polish special services in a democratic state of law.